Time Budget Pressure, Task Complexity, and Dysfunctional Audit Behavior: Role of Audit Fees - Muslim Muslim; Hajering Hajering; Muhammad Faisal AR Pelu; Firda Asrani (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Introduction / Main Objectives: This study aims to analyze the effect of Time Budget Pressure and Task Complexity on Dysfunctional Audit Behavior with Audit Fees as a Moderating Variable at the Makassar City Public Accounting Firm. Methods: The focus of this research was on 39 respondents. This study's research type is quantitative, using primary data. The data collection technique was carried out using a questionnaire. The population of this study was all auditors registered at KAP Makassar City. This research uses field research methods. This study used a survey method to collect field data by distributing questionnaires to research objects. The statistical method used to test the hypothesis is to use multiple linear regression with the help of Smart PLS 3.0 software. The measurement stages carried out are the outer model and inner model tests. Findings / Results: The analysis results show that time budget pressure and task complexity positively and significantly affect dysfunctional audit behavior. Audit fees weaken the effect of time, budget pressure, and task complexity on dysfunctional audit behavior. Conclusions: The implication of this research is to provide input to public accounting firms to evaluate policies that can be carried out to overcome the possibility of dysfunctional behavior.